Democracy-driven governance - Jon Azkune Torres; Mario Zubiaga Garate; Eki Etxebarria Respaldiza (Oñati Socio-Legal Series)
In the following article we analyze the relationship between different governance models and democratisation. To do so, we first address the more structural dimension of the issue. We observe that there is a structural relationship between governance and neoliberal governmentality; however, we find models such as those proposed by Sonia Bussu and Adrián Bua that offer us instruments to think of alternative ways of approaching the issue. Furthermore, we analyze their theoretical framework in relation to consolidated proposals such as Charles Tilly's theory of democracy. Finally, we apply the theoretical concepts to the case of Hernani Burujabe, an innovative case of democracy-driven governance.